2020
DOI: 10.1101/2020.02.24.962605
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-proxy evidence for the impact of the Storegga Slide Tsunami on the early Holocene landscapes of the southern North Sea

Abstract: Doggerland was a land mass occupying an area currently covered by the North Sea until marine inundation took place during the mid-Holocene, ultimately separating the British land mass from the rest of Europe. The Storegga Slide, which triggered a tsunami reflected in sediment deposits in the Northern North Sea, North East coastlines of the British Isles and across the North Atlantic, was a major event during this transgressive phase.The spatial extent of the Storegga tsunami however remains unconfirmed because… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 69 publications
(69 reference statements)
0
6
0
Order By: Relevance
“…PIA and MEGAN were compared in a parallel analysis of seven samples from the Europe's Lost Frontiers project (Gaffney et al, 2020). These samples are from sediment core ELF039 which was taken from a palaeochannel approximately 50 km north of the present Norfolk coast.…”
Section: Analysis Of Empirical Sedadna Datamentioning
confidence: 99%
See 2 more Smart Citations
“…PIA and MEGAN were compared in a parallel analysis of seven samples from the Europe's Lost Frontiers project (Gaffney et al, 2020). These samples are from sediment core ELF039 which was taken from a palaeochannel approximately 50 km north of the present Norfolk coast.…”
Section: Analysis Of Empirical Sedadna Datamentioning
confidence: 99%
“…Every DNA molecule extracted from a sample has the potential to be identified, provided that reference databases are adequate. Second, read count and genome size could be used to calculate biogenomic mass: a proxy of biomass (Gaffney et al, 2020). Third, metabarcoding is far less likely to record DNA damage signals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Storegga tsunami has previously been theorized as having brought about a swift and catastrophic end to Doggerland, the submerged palaeolandscape of the southern North Sea (Weninger et al, 2008). However, a more nuanced understanding is beginning to emerge in the wake of numerical modelling of the wave's dispersal (Hill et al, 2014;Hill et al, 2017), and the discovery of the first confirmed evidence of the tsunami from a submarine context, "core ELF001A" from the "Southern River" submerged river valley, recovered by the Europe's Lost Frontiers team (Gaffney et al, 2020). Clearly the Storegga tsunami hit some of the coastlines of the southern North Sea with considerable force, but the severity of this impact was probably variable (Walker et al, 2020).…”
Section: The Southern North Sea Basinmentioning
confidence: 99%
“…Samples were also extracted for an ongoing environmental study at the University of Warwick as the age and environment of these deposits is compatible with the preservation of ancient DNA (Kistler et al 2017). With the improvement of stratigraphic integrity tests developed at Warwick (Gaffney et al 2019) there is an opportunity to test the environmental composition and extent of DNA movement within each of the cores, a particular concern in terrestrial sedimentary systems (Haile et al 2007). The sedimentary ancient DNA (sedaDNA) profiles may then be used to distinguish late glacial background features and subsequent sequential cuts into the anomalies and their associated palaeoenvironmental reconstructions.…”
Section: Investigating the Durrington Anomaliesmentioning
confidence: 99%